Determination of kaolinite and halloysite crystallite size with X-Ray diffraction: implications for industrial applications - CHRISTIDIS, G.; MAKRl, P. (Bulletin of the Geological Society of Greece, 2001)
Mean thickness and thickness distribution of kaolinite and halloysite clay fractions was obtained by X-ray diffraction, using the Bertaut-Warren-Averbach (BWA) technique, which determines the coherent scattering domain (CSD). Mean thickness of kaolinite and halloysite was 11.8 nm and 10.6 nm respectively and both minerals are characterized by lognormal thickness distribution. Laser scattering, which is often used by the industry, yielded considerably greater mean grain size and bimodal size distribution for both materials due to particle agglomeration. Agglomeration affects optical properties of mineral powders such as brightness adversely, because of light diffusion. A greater discrepancy in particle size determined by the two techniques might explain lower brightness observed in white powders.